HUBUNGAN RIWAYAT KEKURANGAN ENERGI KRONIK SAAT HAMIL DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH PUSKESMAS PENANGGAL KABUPATEN LUMAJANG - Pratiwi, Revita Widya; Ilmiah, Widia Shofa; Indriati, Ina (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
If pregnant women experience malnutrition, the fetus in the womb will be hindered in its growth and development. Hindered fetal growth and development will put the baby at risk of being born with low birth weight. Low birth weight is one of the risk factors for stunting in toddlers. This study aims to determine the relationship between the history of chronic energy deficiency in pregnant women and the incidence of stunting in toddlers in the Penanggal Community Health Center area, Lumajang Regency. This research is a quantitative study based on a retrospective cohort study approach using an analytic correlation research design with a total sample of 48 respondents selected through Simple Random Sampling technique. The results showed that the majority of respondents in the Penanggal Community Health Center area, Lumajang Regency, did not have a history of chronic energy deficiency, totaling 33 respondents (68.8%), and the majority of respondents had children in the normal category (not stunted), totaling 32 respondents (66.7%). From the analysis using the Contingency test, a p-value of 0.000 was obtained, indicating that α <0.05 and it can be concluded that there is a relationship between the history of chronic energy deficiency in pregnant women and the incidence of stunting in toddlers in the Penanggal Community Health Center area, Lumajang Regency. It is important to pay attention to adequate and balanced nutritional intake during adolescence to pregnancy, and to pay special attention to the nutritional needs of pregnant women to prevent chronic energy deficiency and its negative impact on fetal health and the risk of stunting in the offspring.